Evidence on the capitalized value of merger activity for acquiring firms - Schipper, Katherine; Thompson, Rex (Journal of Financial Economics, 1983)
We measure the impact of acquisitions activity on firm value by differentiating between specific merger events and programs of acquisition activity. Based on a sample of conglomerate acquirers, we find significantly positive abnormal performance associated with the announcement of acquisitions programs and significantly negative performance associated with certain institutional changes of 1967–1970 relating to acquisition activity (the Williams Amendments, the 1969 Tax Reform Act, and APB Opinions 16 and 17). Our results support the hypotheses that acquisitions activity had a favorable ex ante impact on the value of firms announcing an intention to engage in acquisitions, and that some of the institutional changes reduced the expected profitability of future acquisitions activity. The basic results of studies of mergers and tender offers are reviewed and their consistency with our findings highlighted.